Annual Variability of Wing Morphology in Culex sitiens Wiedemann (Diptera, Culicidae) Mosquito Vectors from the Coastal Area of Samut Songkhram Province, Thailand. (3rd March 2019) - Chaiphongpachara, Tanawat; Laojun, Sedthapong
Abstract : Culex sitiens Wiedemann (Diptera, Culicidae) is a mosquito vector that is found in coastal areas. Effective control of mosquitoes requires knowledge of the biology, ecology, and behavior of the vector as well as of various other aspects, including its morphology. Currently, variations in the wing size and shape of coastal Cx. sitiens have not been described. Here, morphological changes were studied in the wings of Cx. sitiens from a coastal area of Samut Songkhram Province, Thailand. Samples were collected at night (6:00 pm–6:00 am) during single weeks of September in the years 2015–2017 using Center for Disease Control light traps with dry ice as bait. Eighteen landmarks of each individual were selected and digitized for landmark-based geometric morphometric analyses. Wing size variability was estimated using the isometric estimator of centroid size. Wing-shape variables were computed as Procrustes superimposition with residual coordinates of the 18 landmarks following a Generalized Procrustes Analysis and the principal components of residual coordinates. Degrees of wing-shape dissimilarity among individuals were analyzed using discriminant analysis or canonical variate analysis, which was illustrated in a discriminant space of canonical variables. Differences in wing size and shape among populations were calculated using nonparametric permutations based on 1000 runs with Bonferroni correction tests at a p -value of <0.05. The wing sizes and shapes of the mosquitoes differed significantly between observation years in all population groups, as indicated by nonparametric tests (1000 runs) with the Bonferroni correction. Differing rainfall between observation years was related to morphological changes in mosquito populations, presumably reflecting environmental adaptation. Differences in the wing morphology of Cx. sitiens between annual populations reflect adaptation to environmental variables such as rainfall and may affect the potential to act as insect vectors of human disease. These observations may facilitate the development of tools for managing mosquito-borne disease.